Analisis Kebutuhan dan Ketersediaan Air Bersih Kecamatan Darul Imarah Kabupaten Aceh Besar - Listia, Vina; Yulia, Yulia; Muazzin, Mirza (Tameh, 2024)
Fulfilling sterile water requirements is highly dependent on sterile water sources availability. The problem faced every dry season in Darul Imarah was that around 85% areas did not support with sterile water. The people merely have it from drilled wells, so that it is necessary to analyze the need for sterile water until 2033. The aims of this research were to analyze the total need for sterile water in Darul Imarah district area, to investigate whether the reservoir capacity was sufficient for water needs in 2033 and to figure out the existing of water availability met the needs and sufficiency in Darul Imarah district area until 2033. It is hoped that based on the result of this study could provide information and knowledge to Darul Imarah community about the need and availability of sterile water especially for provision and water consumption. The analysis of the projected population and Local Water Company Mountala customers using the arithmetic method resulted sterile water need and availability and reservoir volume. In 2033, the population in this district will achieve 60,965 people with 14,109 customers. The need for sterile water in 2033 based on the increased number of customers and residents was 143.10 liters/second. Broncap Gle Taron's water needs considered still be able to meet the clean water needs for the current service area until 2033. This was proven by the total clean water need in 2023 would be 150 liters/second. The reservoir required in 2033 would be 2472.83 m3. The reservoir storage volume at Local Water Company Mountala was 1 unit with storage of 500 m3. The shortage of reservoir capacity was 1972.83 m3 or it requires 4 additional reservoir units to meet water availability in 2033. The need for sterile water increasing every year to minimize water shortages, so it is necessary to consume water effectively.